Molecular detection of methicillin-resistant Staphylococcus aureus (MRSA) - Erkihun Aklilu; Nur Hardy Bin Abu Daud; Mohd Mokhtar Bin Arshad; Siti Rokiah Binti Awang (2015)

(untitled)
Multi-drug resistant staphylococci including methicillin-resistant Staphylococcus aureus